2008
DOI: 10.1128/aac.01456-07
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Biapenem and Tebipenem Complexed with Penicillin-Binding Proteins 2X and 1A from Streptococcus pneumoniae

Abstract: Biapenem is a parenteral carbapenem antibiotic that exhibits wide-ranging antibacterial activity, remarkable chemical stability, and extensive stability against human renal dehydropeptidase-I. Tebipenem is the active form of tebipenem pivoxil, a novel oral carbapenem antibiotic that has a high level of bioavailability in humans, in addition to the above-mentioned features. ␤-lactam antibiotics, including carbapenems, target penicillin-binding proteins (PBPs), which are membrane-associated enzymes that play ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…The methyl group is reported to give resistance to degradation by dehydropeptidase-1; however, these results are the first data showing that the group has an influence on the resistance resulting from PBP2 mutations. According to the co-crystal structure of PBP2x from S. pneumoniae and BIPM, the side chain of T550 forms hydrogen bonds with the oxygen atoms at the third position in the ring of BIPM (Yamada et al, 2008). In E. coli, dependency on this hydrogen bond might be strong for 1-b-methyl carbapenems, because the susceptibilities to PBP2 mutants were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The methyl group is reported to give resistance to degradation by dehydropeptidase-1; however, these results are the first data showing that the group has an influence on the resistance resulting from PBP2 mutations. According to the co-crystal structure of PBP2x from S. pneumoniae and BIPM, the side chain of T550 forms hydrogen bonds with the oxygen atoms at the third position in the ring of BIPM (Yamada et al, 2008). In E. coli, dependency on this hydrogen bond might be strong for 1-b-methyl carbapenems, because the susceptibilities to PBP2 mutants were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The small adjacent N‐terminal segment of the transpeptidase domain comprises two α‐helices [α1n (250–268) and α2n (270–276)] and a three‐stranded [β1n (280–284), β2n (480–486), and β3n (490–495)] antiparallel β‐sheet (Figs 1A and 2). The PonA1 transpeptidase (or penicillin‐binding domain) resembles other PBPs secondary structure: PBP1 of class A from Staphylococcus pneumonia (RMSD of 1.9 Å) 24, 25, the transpeptidase domain of PBP2 from Neisseria gonorroeae (RMSD of 2.00 Å) 26, class A PBP1 from Pseudomonas aeruginosa (RMSD of 1.65 Å) 27, 28, and PBP4 from Listeria monocytogenes (RMSD of 2.01 Å) 29. A cleft in the middle of the domain contains the active site.…”
Section: Resultsmentioning
confidence: 99%
“…5 Crystallographic structures revealed that the carbapenem C-2 side chains form non-polar interactions with the side chains of Trp374 and Thr526 of PBP2X and with those of Trp411 and Thr543 of PBP1A. Because ME1036 possesses an imidazo [5,1-b]thiazole moiety at the C-2 position, it may also interact with the respective tryptophan and threonine residues of PBP1A and PBP2X in a similar manner, which would result in strong binding affinities.…”
Section: Antimicrobial Activity and Affinities To Pbps Y Hirai Et Almentioning
confidence: 99%